2021
DOI: 10.5709/ce.1897-9254.469
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Economic Indicators in the Context of Financial and Economic Crises

Abstract: Financial and economic crises repeat themselves at indefinite intervals. As in the Great Recession (also known as Subprime Crisis) of 2007/2008 there was a bundle of events and processes that preceded it and contributed to its emergence, whether it be economic, political, or ideological. Based on observations presented in this paper, explanations are suggested that crises are significantly related to the development of various indicators. Relevant indicators include the impact of economic indicators (e.g., GDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The increasing level of uncertainty in economic growth provides room for economists to find out the origin of this phenomenon and to link it to its causal relationship with the real economy (Kesselman,et al2015). The strong economic turmoil in the global financial crisis of 2007-2008 and the drastic economic downturn that occurred both in the United States and in other countries have cast great doubt on the fluctuations of the business cycle (Sinkovic, Zemla, & Zemla, 2022). Several studies have shown that empirically the combination of financial shocks and economic uncertainty simultaneously causes business cycle fluctuations (Houari, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing level of uncertainty in economic growth provides room for economists to find out the origin of this phenomenon and to link it to its causal relationship with the real economy (Kesselman,et al2015). The strong economic turmoil in the global financial crisis of 2007-2008 and the drastic economic downturn that occurred both in the United States and in other countries have cast great doubt on the fluctuations of the business cycle (Sinkovic, Zemla, & Zemla, 2022). Several studies have shown that empirically the combination of financial shocks and economic uncertainty simultaneously causes business cycle fluctuations (Houari, 2022).…”
Section: Introductionmentioning
confidence: 99%